2019
DOI: 10.1029/2018gl079071
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Extratropical Cyclone Strength and Atmospheric River Intensity and Position

Abstract: Extratropical cyclones (ECs) and atmospheric rivers (ARs) impact precipitation over the U.S. West Coast and other analogous regions globally. This study investigates the relationship between ECs and ARs by exploring the connections between EC strength and AR intensity and position using a new AR intensity scale. While 82% of ARs are associated with an EC, only 45% of ECs have a paired AR and the distance between the AR and EC varies greatly. Roughly 20% of ARs (defined by vertically integrated water vapor tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(163 citation statements)
references
References 42 publications
7
142
0
Order By: Relevance
“…It is an indicative that the remote moisture sources may have an important contribution to the subtropical cyclone development as previously discussed by Reference [46]. The role of external moisture sources has been emphasized in tropical [47] and extratropical [48,49] cyclogeneses. The moisture travels from its source to the cyclone region like a corridor in the lower atmosphere [48], which is called conveyor belt or atmospheric river.…”
Section: Synoptic Analysismentioning
confidence: 57%
See 1 more Smart Citation
“…It is an indicative that the remote moisture sources may have an important contribution to the subtropical cyclone development as previously discussed by Reference [46]. The role of external moisture sources has been emphasized in tropical [47] and extratropical [48,49] cyclogeneses. The moisture travels from its source to the cyclone region like a corridor in the lower atmosphere [48], which is called conveyor belt or atmospheric river.…”
Section: Synoptic Analysismentioning
confidence: 57%
“…The moisture travels from its source to the cyclone region like a corridor in the lower atmosphere [48], which is called conveyor belt or atmospheric river. For extratropical cyclones, the atmospheric rivers contribute to deepening these systems by providing more water vapor for latent heat release [49].…”
Section: Synoptic Analysismentioning
confidence: 99%
“…Atmospheric rivers (ARs) are elongated regions of intense horizontal water vapor transport, which are often associated with a baroclinic midlatitude cyclone (Neiman et al, ; Ralph et al, ; Ralph et al, ; Zhang et al, ; Zhu & Newell, ). Many studies have revealed the important link between ARs and annual precipitation over different regions around the globe (Dettinger et al, ; Lavers et al, ; Ralph & Dettinger ; Neiman et al, ; Lavers & Villarini, ; Lamjiri et al, ; and others), their association with global floods and water availability (Ralph et al, ; Leung & Qian, ; Ralph & Dettinger ; Paltan et al, ; Corringham, ), their relationship to snowpack over the western U.S. (Goldenson et al, ; Guan et al, ; Huning et al, , ), their importance to extratropical climate and hydrology (Gorodetskaya et al, ; Nash et al, ), and their projected changes in a warming climate (e.g., Espinoza et al, ; Guirguis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…dT (26) where ∆T e p is the surface temperature differences between the pole and the equator. First, we consider the partial sensitivity coefficients which reflect the sensitivity of n with respect to T, ∆T e p and Γ:…”
Section: Qualitative Analysismentioning
confidence: 99%
“…One of the main dynamical mechanisms leading to the meridional transport of heat, moisture, and momentum from the tropical to polar latitudes and, thereby to the global redistribution of atmospheric moisture, are the large-scale extratropical eddies (cyclones) [19][20][21][22]. The so-called "atmospheric rivers" that transport water vapor outside of the tropics through the extratropics (middle latitudes) are associated with mid-latitude cyclonic eddies and their frontal zones [25,26]. Recent studies have indicated an increase in intensity of extratropical cyclones and a decrease in their frequency [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%